Ocimum Tenuiflorum Linne: A Narrative Review - Kasmara, Dwi Pratiwi; Singarimbun, Nurbaiti Br.; Perangin-Angin, Susi Amenta Beru (International Journal of Nursing Information, 2024)
Indonesia's diverse flora offers significant potential for medicinal plant production, yet reliance on anecdotal experiences prompts a deeper examination. This study focuses on Ruku-ruku (Ocimum Tenuiflorum Linne), traditionally a culinary herb in West Sumatra. Despite its local culinary use, Ruku-ruku remains largely unexplored for medicinal properties, emphasizing the importance of phytochemical screening to uncover its therapeutic potential. Ocimum Sanctum, known as Holy Basil or Tulsi, holds sacred status in India and boasts a rich history documented in ancient medical texts. This study aimed to review the evidence for therapeutic efficacy and botanical and chemical aspects. The research methodology, employing a narrative literature review, assesses 40 studies (2015-2023). Results underscore Tulsi's holistic benefits, covering metabolic disorders, cardiovascular and cognitive health, infections, cancer prevention, oral health, wound healing, and weight management. Diverse formulations, from essential oils to capsules and gels, highlight the extensive applications of Ocimum Tenuiflorum Linne. The study explores botanical and chemical aspects, including shoot induction and essential oil extraction. Ocimum Sanctum's adaptogenic and antimicrobial properties are discussed, showcasing its potential under stress conditions and against various infections. In conclusion, this review stresses the vast therapeutic potential of Ocimum Tenuiflorum Linne, urging further research to unlock its full medicinal benefits. Integrating traditional wisdom with modern science positions these plants as valuable subjects for pharmaceutical and medicinal applications, potentially addressing contemporary health challenges, including the COVID-19 pandemic. This research contributes to providing information about Ocimum Tenuiflorum Linne and its benefits for health care as therapeutic properties.